Pelaksanaan Pendidikan Agama Membentuk Karakter Anak di SD Negeri Candi 02 Semarang - Jaelani, Rifky Rasyid; Sukoco, Sukoco; Hadi, Agustinus Sutriyanto (Journal of Democratia; Vol 3 No 1 (2025): Jurnal Democratia : Pendidikan Pancasila dan Kewarganegaraan, Moral, Karakter, dan HukumDO - 10.31331/jade.v3i1.3621, 2024)
This research is motivated by the author's attention to the importance of admirable qualities in a human being. The focus studied in this research is religious education in forming children's noble qualities. This research uses a qualitative approach with a phenomenological type. The data collection techniques used are in-depth interview techniques, observation and documentation. Data analysis used the interactive model from Huberman and Miles including data reduction, data presentation, and drawing conclusions. Checking the validity of the data uses data source triangulation and method triangulation.The results of the research show that: (1) Religious education is very important in forming children's noble character: (2) The implementation of religious education in forming character at Candi 02 State Elementary School is running well and the methods used are subjective in that each institution, teacher, and parents have their own methods in educating students; (3) children are able to implement the knowledge they have learned into their daily lives; (4) inhibiting factors can include: first, the problem of children who like to play with gadgets. This occurs outside the learning environment of educational institutions.